Pengaruh Komunikasi, Disiplin Kerja, Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan - Isnaeni Rokhayati; Heri Setiawan; Brian Jordi Bagaskara (FEB UNWIKU PURWOKERTO, 2022)
The purpose of this research is to find out and analyze the influence of communication, work discipline, leadership style and work environment on employee performance. This is a case study at the Administrative Staff Office, Faculty of Law, Jenderal Sudirman University. The research uses primary data obtained by using questionnaires and direct interviews with research respondents. The population in this study amounted to 36 employees. The sampling technique used is disproportionate stratified random sampling and obtained as many as 33 employees as respondents. The analytical method used is multiple linear regression analysis. Based on the analysis results indicate that the communication variable has a significant positive effect on employee performance, this can be evidenced by the value of t count (4.578) > t table (2.048). Then the work discipline variable has a significant positive effect on employee performance, this can be proven by the value of t count (2.584) > t table (2.048). While the variable leadership style has a significant positive effect on employee performance, this can be proven by the value of t count (3.828) > t table (2.048). And the work environment variable has a significant positive effect on employee performance, this can be proven by the value of t count (3.407) > t table (2.048). The implication of this research is that communication between fellow employees must be clearer when providing explanations about the tasks to be carried out, there needs to be an increase in discipline, especially in accuracy in carrying out tasks so that tasks are not repaired much and can be completed on time, leaders must create patterns of relationships and communication. lighting in the room is sufficient, employees will feel comfortable and more focused in doing their work. The limitation of this research is data collection using questionnaires, sometimes the answers given are not in accordance with the actual situation. Suggestions for further researchers is to add variables to be studied such as work motivation, work commitment and so on.